2005
DOI: 10.1002/path.1708
|View full text |Cite
|
Sign up to set email alerts
|

Cell‐cycle‐dependent regulation of DNA replication and its relevance to cancer pathology

Abstract: The highly orchestrated process of DNA replication ensures the accurate inheritance of genetic information from one cell generation to the next. The exact execution of DNA replication depends on a large number of proteins that are being studied extensively in the cell cycle field. Some of these proteins, such as the minichromosome maintenance proteins (MCMs), are essential for the process of DNA replication itself. Others such as geminin are specifically required to limit DNA replication to once per cell cycle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
124
0
10

Year Published

2005
2005
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(143 citation statements)
references
References 45 publications
9
124
0
10
Order By: Relevance
“…This fact could also explain why the blastoid and classical subtype had no significant difference in the MCM6 expression as a marker for the G1 arrest and not as a proliferation marker. As this cell cycle arrest has been shown by others Eward et al, 2004;Obermann et al, 2005;Tachibana et al, 2005), we could demonstrate that this has a clinical relevance in patients with MCLs. Our data on expression of repp86 in MCL (Schrader et al, 2005) showed that real proliferation activity is an important prognostic factor in MCL.…”
Section: Discussionsupporting
confidence: 78%
“…This fact could also explain why the blastoid and classical subtype had no significant difference in the MCM6 expression as a marker for the G1 arrest and not as a proliferation marker. As this cell cycle arrest has been shown by others Eward et al, 2004;Obermann et al, 2005;Tachibana et al, 2005), we could demonstrate that this has a clinical relevance in patients with MCLs. Our data on expression of repp86 in MCL (Schrader et al, 2005) showed that real proliferation activity is an important prognostic factor in MCL.…”
Section: Discussionsupporting
confidence: 78%
“…To further establish the role of Chk1 in G 2 arrest, it was necessary to resolve whether the ΔChk1 cells observed by flow cytometry as arrested in G 2 /M were in fact in G 2 or M. Geminin is a marker of cells in S and G 2 ; it is proteolyzed in mitosis and does not accumulate again until cells enter S. 36 While phosphorylation of histone H3 is frequently used as a marker of mitosis, this is only a transient signal that can not be used to detect post-mitotic tetraploid cells. This limitation is resolved by using geminin.…”
Section: Resultsmentioning
confidence: 99%
“…Geminin, a novel proliferation marker is present from the G 1 -S transition to early M phases (McGarry and Kirschner, 1998) and helps to regulate cell-cycle initiation by impeding a second prereplication complex assembly once replication has started (McGarry and Kirschner, 1998;Tachibana et al, 2005). It has also been suggested that geminin levels may be altered in cancer cells as it has been found to be overexpressed in several cancer cell lines (Xouri et al, 2004).…”
mentioning
confidence: 99%